Design Consolidate Cost Accounting System For Economic Entities - الجبوري, نصيف جاسم; بيجان, رجاء صادق (Journal of Economics and Administrative Sciences, 2014)
The Costing Accounting is one the analytic tools which plays important role by support the management in planning&  control and decisions-making ,as it became attendant necessity to establish any project whether industrial ,commercial ,service or agriculture ..etc.     The consolidated accounting system has committed the companies to have their active costing system in which the management can obtain their own data, but we found most of the economic units face problems of applying the costing system because of reasons related to the system design itself or might be related to the requirements of the application success.        So the study has been prepared for the potentiality  to set and designing Consolidated Costing System that provides relevant  information for proper  decision-making, So the need has been emerged in practical realism to review the costing  system that came with the Consolidated Accounting System specially since increasing the demand for information and the changes that occurs in business environments and the insistence to perform competitive advantageous.  Al-Kut General  Company For Textile Industries has been selected as a field to apply this study due to its importance on industrial sector level, in addition to experience of the company and its potentialities as well Through studying the truth  of current costing system and identifying the weaknesses & strength points ,also create model for a Consolidated Costing System that fits the nature of cost centers and products too.     The system has been applied and the outputs  has compared  in form that shows the information and the styles that is created from applying the new system shall be more efficient and important in serving  the management to provide all requirements for information.